Expression of CD39 Is Correlated With HIV DNA Levels in Naïve Tregs in Chronically Infected ART Naïve Patients - Song, Jin-Wen; Huang, Hui-Huang; Zhang, Chao; Yang, Hong-Ge; Zhang, Ji-Yuan; Xu, Ruo-Nan; Jin, Lei; Shi, Ming; Wang, Fu-Sheng; Jiao, Yan-Mei (Frontiers in Immunology, 2019)
Abstract Background: Treg cells represent important viral reservoirs during chronic HIV infection. CD39 is closely involved in Treg-mediated immunosuppressive effects. However, CD39 expression on nTregs and mTregs and a relationship with HIV DNA levels during HIV infection is still unclear. In this study, we analyzed the distribution of HIV DNA in Treg subsets and the association between HIV DNA and CD39 expression on Treg subsets. Methods: Sixty-two HIV-infected patients with different HIV stages and 14 uninfected individuals were enrolled. nTregs (CD4+CD25+CD127lowCD45RO-) and mTregs (CD4+CD25+CD127lowCD45RO+) were isolated by magnetic selection and flow cytometric sorting. HIV DNA was quantified by real-time polymerase chain reaction (PCR). CD39 expression on nTregs and mTregs was analyzed by flow cytometry. Results: Higher levels of HIV DNA were detected in mTregs than those in nTregs during chronic HIV infection. The frequency of CD39+ nTregs and HIV DNA levels in nTregs were increased in patients with advanced HIV infection. Furthermore, HIV DNA levels in nTregs correlated positively with CD39+ nTreg frequency. CD39+ nTreg frequency was also increased in immune non-responders. Conclusions: mTregs and nTregs are both important reservoirs of virus during chronic HIV infection and HIV DNA levels increase in nTregs in patients with advanced HIV infection.